Brazil - 2022 Investment Policy and Regulatory Review - World Bank Group (World Bank, Washington, DC, 2022)
This investment policy and regulatory review (IPRR) presents information on the legal and regulatory frameworks governing foreign direct investment (FDI) in Brazil. Since legal and regulatory frameworks are constantly evolving, a cut-off date was set for the research. This country review, therefore, covers information available as of December 31, 2021, unless otherwise indicated in the review. IPRRs are available for the following middle-income countries (MICs): Brazil, China, India, Indonesia, Malaysia, Mexico, Nigeria, Thailand, Turkey, and Vietnam. This IPRR is organized as follows: section 1 gives an introduction. Section 2 provides an overview of the country’s investment policy framework, including the legal instruments regulating foreign investment, key institutions involved in investment promotion, as well as the country’s foreign investment promotion strategy; it also delineates the country’s international investment legal framework, including the country’s commitments under the World Trade Organization (WTO) and select international investment agreements (IIAs); sections 3 to 6 cover the country’s policies and domestic legal framework concerning different dimensions of the lifecycle of an investment: entry and establishment (section 3), protection (4), incentives (5) and linkages (6); sections 7 and 8 explore emerging investment policy and regulatory areas. Section 7 considers outward FDI and section 8 responsible investment. Section 9 focuses on city-specific investment policy and regulatory measures in the largest commercial center; and section 10 covers FDI in the digital economy.